2023
DOI: 10.3389/fmicb.2023.1169809
|View full text |Cite
|
Sign up to set email alerts
|

From salty to thriving: plant growth promoting bacteria as nature’s allies in overcoming salinity stress in plants

Abstract: Soil salinity is one of the main problems that affects global crop yield. Researchers have attempted to alleviate the effects of salt stress on plant growth using a variety of approaches, including genetic modification of salt-tolerant plants, screening the higher salt-tolerant genotypes, and the inoculation of beneficial plant microbiome, such as plant growth-promoting bacteria (PGPB). PGPB mainly exists in the rhizosphere soil, plant tissues and on the surfaces of leaves or stems, and can promote plant growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 158 publications
(150 reference statements)
0
4
0
Order By: Relevance
“…Arid and semi-arid areas are among the most vulnerable to environmental constraints that are exacerbated by climate change. Salinity is a relevant environmental limiting element, causing major reductions in plant productivity (Peng et al 2023 ; Raza et al 2022 ). It is estimated that more than 50% of the arable soils in the world will be salinized by 2050 (Etesami et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arid and semi-arid areas are among the most vulnerable to environmental constraints that are exacerbated by climate change. Salinity is a relevant environmental limiting element, causing major reductions in plant productivity (Peng et al 2023 ; Raza et al 2022 ). It is estimated that more than 50% of the arable soils in the world will be salinized by 2050 (Etesami et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although P. sativum is recognized to be moderately tolerant to soil salinity (Shahid et al 2022 ), elevated salt levels in soil were reported to significantly affect its productivity (Noreen and Ashraf 2009 ). In previous few years, inoculation of plants with beneficial soil microbes, including plant growth-promoting bacteria (PGPB), has proven to be a useful approach to enhance sustainable agriculture in soils subjected to several abiotic stresses, including salinity (Bhat et al 2023 , 2020 ; Peng et al 2023 ; Mishra et al 2021 ). They can increment the germination of seeds as well as the leaf size, improve chlorophyll and protein amount, increase crop growth and yield, in addition to nutrient accessibility, and delay the senescence of leaves (Saghafi et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some beneficial rhizobacteria can also suppress plant diseases by producing antimicrobial compounds, competing with pathogens for resources, and inducing systemic resistance [15,16]. Additionally, they help plants cope with abiotic stress by inducing systemic tolerance [17] (Figure 1). In this review, we focus on the roles of root exudates in the colonization process of beneficial soil rhizobacteria.…”
Section: Introductionmentioning
confidence: 99%